PENGELOLAAN KEPERAWATAN GANGGUAN VOLUME CAIRAN DAN ELEKTROLIT; KURANG DARI KEBUTUHAN PADA PASIEN ANAK DIARE DENGAN DEHIDRASI SEDANG DI RSUD BATANG - Hartono, Mardi; Badrudin, Muhammad; Djoko Santoso, Petrus Nugroho (Poltekkes Kemenkes Semarang, 2021)
Background : Diarrhea is defecation with a liquid or half liquid stool with a frequency of more than 3 times per day and can be accompanied or without lenders and blood. In diarrhea children the need for rehydration must be fulfilled immediately to minimize the risk of complications.Purpose : This study aims to be able to report on the management of nursing care, able to describe and analyze the results of studies, nursing problems, planning, nursing care actions, and evaluation of actions taken to overcome fluid volume shortages with dehydration while in two diarrhea pediatric patients.Method : This Scientific Writing uses descriptive research methods that have the purpose of describing and enforcing facts in managing nursing fluid volume disorders: less than the need for diarrhea children with moderate dehydration.Result : In patients lacking fluid volume there are several measures to overcome the lack of fluid volume, one of which is by rehydrating and monitoring fluid balance in patients. After nursing action, the results obtained were the presence of an improved hydration status response from the presence of fluid balance in both patients.Conclusion : In conclusion, the application of rehydration measures and monitoring of fluid balance in patients with moderate dehydration diarrhea with impaired fluid and electrolyte volumes must be carried out comprehensively so that the planned goals and outcome criteria can be achieved.Â Keywords: diarrhea, lack of fluid volume, rehydration